Ethnic conflict: a global perspective - Wolff, Stefan (Oxford, 2006)
Why is it that Catholics and Protestants in Northern Ireland have been in perpetual conflict for thirty years when they can live and prosper together elsewhere? Why was there a bloody civil war in Bosnia and Herzegovina when Croats, Serbs, and Muslims had lived peacefully side-by-side for decades? Why did nobody see and act upon the early warning signs of genocide in Rwanda that eventually killed close to a million people in a matter of weeks? What is it that makes Kashmir potentially worth a nuclear war between India and Pakistan? In recent years hardly a day has gone by when ethnic conflict in some part of the world has not made headline news. The violence involved in these conflicts continues to destabilize entire regions, hamper social and economic development, and cause unimaginable human suffering. And the extensive media coverage of these conflicts all too often raises important questions that it signally fails to answer. This book aims to fill this gap. Drawing on the author's long experience of studying such conflicts around the world and his involvement in attempts to resolve them, it provides an illuminating and accessible introduction to the origins, dynamics, and management of ethnic conflict. In doing so, it helps explain the fundamental question underlying all these conflicts: why do nationalism and ethnicity still have such terrible power to turn neighbour against neighbour?
Keywords: Ethnicity and nationalism